Social Preference Tests in Zebrafish: A Systematic Review - Ogi, Asahi; Licitra, Rosario; Naef, Valentina; Marchese, Maria; Fronte, Baldassare; Gazzano, Angelo; Santorelli, Filippo M. (Frontiers in Veterinary Science, 2021)
The use of animal models in biology research continues to be necessary for the development of new technologies and medicines, and therefore crucial for enhancing human and animal health. In this context, the need to ensure the compliance of research with the principles Replacement, Reduction and Refinement (the 3 Rs), which underpin the ethical and human approach to husbandry and experimental design, has become a central issue. The zebrafish (Danio rerio) is becoming a widely used model in the field of behavioral neuroscience. In particular, studying zebrafish social preference, by observing how an individual fish interacts with conspecifics, may offer insights into several neuropsychiatric and neurodevelopmental disorders. The main aim of this review is to summarize principal factors affecting zebrafish behavior during social preference tests. We identified three categories of social research using zebrafish: studies carried out in untreated wild-type zebrafish, in pharmacologically treated wild-type zebrafish, and in genetically engineered fish. We suggest guidelines for standardizing social preference testing in the zebrafish model. The main advances gleaned from zebrafish social behavior testing are discussed, together with the relevance of this method to scientific research, including the study of behavioral disorders in humans. The authors stress the importance of adopting an ethical approach that considers the welfare of animals involved in experimental procedures. Ensuring a high standard of animal welfare is not only good for the animals, but also enhances the quality of our science.